Hyperkalemia and Dialysis in the Deployed Setting. (5th September 2018) - Stewart, Ian J; Bolanos, Jonathan A; Little, Dustin J; Chung, Kevin K; Sosnov, Jonathan A; Miller, Nancy; Poirier, Mark D; Saenz, Kristin K; McAlister, Vivian C; Moghadam, Soraya; Kao, Ray; Stockinger, Zsolt T
Abstract: Acute kidney injury is a recognized complication of combat trauma. The complications associated with acute kidney injury, such as life-threatening hyperkalemia, are usually delayed in onset. In the recent conflicts, rapid evacuation of U.S. and coalition personnel generally resulted in these complications occurring at higher echelons of care where renal replacement therapies were available. In the future however, deployed providers may not have this luxury and should be prepared to temporize patients while they await transport. In this clinical practice guideline, recommendations are made for the management of patients with, or at risk for, acute kidney injury and hyperkalemia in the austere, deployed environment.